STAGES OF HEATING AND COOLING OF FRICTION PAIRS OF BRAKE DEVICES - Volchenko, Dmytro; Kindrachuk, Myroslav; Demyanchuk, Yaroslav; Vozniy, Andriy; Burava, Oleksandr; Pryyazhny, Andriy; Nishchuk, Viktor (Problems of Friction and Wear, 2024)
In the process of intense electrical-thermo-mechanical loading of friction pairs of braking devices, which take place on transport, technological equipment, etc., the surface-volume temperatures of their elements can reach significant values, at which the thermophysical properties of the surface and subsurface layers of materials change significantly. Their change is influenced by surface and deep temperature gradients, as well as heating rates and forced air cooling of friction brake elements. Theoretical and experimental studies of the energy load of various types of friction brake units under pulsed and long-term braking modes made it possible to determine the surface and deep temperature gradients, as well as the rate of heating and forced air cooling of the friction elements, and it was established: the most common with local contact of microprotrusions the emerging fields of current lines is the thermodynamic potential, which includes external and internal parameters in their working layers; the thermodynamic potential is determined by the conditions of thermodynamic equilibrium of the tribosystem and the criteria for its stability in a variety of processes accompanied by changes in energy; a local area of actual contact of microprotrusions, formed by the simultaneous action of normal and tangential impulse loads, causing electric and thermal currents that do not completely disappear when the pulsed specific loads are removed, forming frictional connections of microprotrusions; the magnitude of surface and deep temperature gradients and their limitations for metal friction elements, as well as the rates of heating and cooling, knowledge of which allows us to move on to the patterns of changes in the thermophysical parameters of friction pair materials. The regularities of changes in surface and deep temperature gradients and rates of heating and forced air cooling of metal friction brake elements have been established.